Options for a Low Carbon Energy Future in Morocco - World Bank (Washington, DC, 2013)
Morocco s economy is growing rapidly in all its sectors (tourism, agriculture, industry , etc.) Consequently, the energy demand has been increasing steadily in the period 2003-2007 when primary energy demand rose by 5% per annum and electricity demand by 8% per annum. At the request of the World Bank Group, this study was launched having 3 main objectives: An analysis of the current characteristics of energy supply and demand, the assessment of the energy strategy of Morocco for the coming years, and then a development of an alternative energy scenario with low carbon energies. Beicip-Franlab has established a detailed energy balance of Morocco on the basis ofMoroccan and international studies already conducted on the energy sector of Morocco as well as on well known databases like IEA ones.For the period 2009-2030, Morocco has defined an energy strategy which was presented during the first Assises de l Energie organized in March 2009. An assessment of this strategy considering both energy and environmental criteria will be presented in order to be compared with the business as usual scenario.Finally an alternative scenario is proposed. Based on an intensive introduction ofrenewable energy (RE) and energy efficiency (EE), this scenario would permit a great exploitation of the available RE potential in Morocco, and particularly its wind power potential. In November 2009 after the present report is finalized, Moroccan authorities presented a solar power plan which increases its renewable energy target in 2020, making solar energy target comparable to its wind energy target.A quick review of this new solar plan is presented at the end of this report.